Super-resolution localization microscopy of radiation-induced histone H2AX-phosphorylation in relation to H3K9-trimethylation in HeLa cells - Hausmann, Michael; Wagner, Emma; Lee, Jin-Ho; Krufczik, Matthias; Papenfuß, Franziska (Nanoscale, 2018)
Ionizing radiation (IR)-induced damage confers functional and conformational changes to nuclear chromatin associated with DNA single and double strand breaks. This leads to the activation of complex DNA repair machineries that aim to preserve the integrity of the DNA molecule. Since hetero- and euchromatin are differentially accessible to DNA repair pathways, local chromatin re-arrangements and structural changes are among the consequences of an activated DNA damage response. Using super-resolution localization microscopy (SRLM), we investigated the X-ray-induced repositioning of γ-H2AX and histone H3K9me3 heterochromatin marks in the nuclei of HeLa cells. Aliquots of cells exposed to different IR doses (0.5, 1 and 2 Gy) were fixed at certain repair times for SRLM imaging. The number and size of nano-scale γ-H2AX molecule signal clusters detected increased with rising irradiation doses, with the number and size being the highest 0.5 h after irradiation. With growing repair time both the number and size of γ-H2AX nano-clusters decreased. Eight hours after irradiation, the number of clusters reached control levels, in agreement with the disappearance of most IR-induced foci seen by conventional microscopy. SRLM investigation of heterochromatin marks in spatial relation to γ-H2AX clusters showed that on average the heterochromatin density was high in the vicinity of γ-H2AX, which is in agreement with the observation that DSBs seem to relocate to the surface of heterochromatin clusters for DNA repair. The data demonstrate the potential of pointillist images obtained by SRLM for quantitative investigations of chromatin conformation changes and repair-protein recruitment on the nanoscale as measures for a radiation response.
Gesehen am 22.10.2019